Antidiabetic potential of Gaultheria trichophylla in mice - Alam, Fiaz; Saqib, Qazi Najam us (Bangladesh Journal of Pharmacology, 2017)
This study evaluated Gaultheria trichophylla for its in vitro and in vivo anti-diabetic activity and its effect on biochemical parameters. The extract inhibited ?-glucosidase with IC50 = 17.5 ± 0.1 ?g/mL). The difference of body weight of the extract-treated diabetic groups and diabetic control was significant (p<0.05). The extract-treated and the standard-treated groups showed significant (p<0.001) decrease in the fasting blood glucose levels compared to diabetic control. The extract-treated groups after 15 days of treatment showed a significance (p<0.001 and p<0.05) decrease of the urea and creatinine levels respectively. The extract and standard-treated diabetic groups showed a significant decreased in the serum level of cholesterol, LDL, and triglycerides compared to the diabetic control group (p<0.001). The extract and standard drug showed a significance improvement of HDL level in diabetic mice compared to the diabetic control (p<0.001). Video Clip of Methodology: 2 min 49 sec: Full Screen Alternate